تقييم فيتامين (د) والكالسيوم عند النساء الحوامل في بعض مستشفيات ترهونة - نورا اللافي عبد الله (Surman Journal of Science and Technology, 2025)
After both calcium and vitamin D, one of the essential elements for women،s health, as they play a pivotal role in supporting bone and dental health for both the mother and the fetus. Vitamin D deficiency is common during pregnancy, especially between groups of pregnant women with limited exposure to sunlight. And vitamin D deficiency during pregnancy may lead to healthy complications such as pre-eclampsia, gestational diabetes, low birth weight, its deficiency may also be linked to an increased risk of preterm birth and the weakness of the fetus growth. This study aimed to assess the levels of calcium and vitamin D in the blood serum in pregnant women in the city of Tarhuna, this study was conducted in a number of private clinics and laboratories and Tarhuna General Hospital, and included 87 women, including 67 pregnant women (20 women in the first trimester, 27 women in the second trimester, 20 women in the third trimester) and 20 non-pregnant women. Women with chronic diseases such as heart disease, diabetes, chronic kidney disease, or chronic liver disease and women taking vitamin D and calcium supplements were excluded. 5 ml of venous blood was collected from all the women in the study, and the blood was separated by a centrifuge and divided the serum into 2 tubes designed to analyze both vitamin D and calcium. To determine the concentration of vitamin D it was done using I-CHROMA device. The calcium level was determined using a device (4040) SPECTOPHOTOMETER. The results showed no significant decrease (P>0.05) in level of vitamin D and calcium at pregnant women depends on age, different months of pregnancy. There are significant differences (P<0.05) in the level of vitamin D at pregnant women according to the number of births (among pregnant women who are experiencing their first birth compared to multiparous pregnant women), and there were no significant differences (P>0.05) in the level calcium at pregnant women depending on the number of births. There was no significant decrease (P>0.05) in the level of calcium and vitamin D at pregnant women compared to non-pregnant women.